Electrochemically nanotuned surface comprising 3D bimetallic dendrites fabricated on MWCNT for detection of 1,4-dioxane in water - Kumari R.; Dkhar D.S.; Chandra P. (My University, 2025)
Water quality has become one of the most serious environmental problems throughout the globe. The recalcitrant molecule, 1,4-Dioxane (1,4-D) has been recognized as a pollutant of rising concern in water, according to the World Health Organization (WHO), and can cause harm to aquatic organisms, animals, and even humans. Thus, it is important to detect 1,4-D in water bodies accurately and sensitively. In light of this, by fine-tuning the electrodeposition conditions, a novel bimetallic copper and gold nanodendritic structure was fabricated on the multiwalled carbon nanotube (MWCNT) functionalized glassy carbon electrode (GCE). The nanosensor was characterized by several physical and electrochemical techniques. The sensor probe exhibits good analytical performance and possess linear dynamic ranges (LDR) between 5 to 103 nM and 0.5 × 105 to 2 × 105 nM. The sensor showed limit of detection (LOD) and limit of quantification (LOQ) of 3.27 ± 0.04 pM and 10.92 ± 0.07 pM, respectively, with a mean response time of 1.65 ± 0.05 s. The sensor's performance was analyzed using tap water and Ganga water, with 90.24–99.57 % and 90.05–98.88 % of 1,4-D recovered without interference, respectively. The entire process of fabricating the surface and testing the 1,4-D takes hardly around 30 min, showing the sensor's applicability in monitoring 1,4-D in the environment. © 2023 Elsevier B.V.